Nomogram Predicting the Benefits of Adding Concurrent Chemotherapy to Intensity-Modulated Radiotherapy After Induction Chemotherapy in Stages II–IVb Nasopharyngeal Carcinoma - Liu, Sai-Lan; Sun, Xue-Song; Lu, Zi-Jian; Chen, Qiu-Yan; Lin, Huan-Xin; Tang, Lin-Quan; Bei, Jin-Xin; Guo, Ling; Mai, Hai-Qiang (Frontiers in Oncology, 2020)
Background: To compare the efficacy of induction chemotherapy plus concurrent chemoradiotherapy (IC+CCRT) versus induction chemotherapy plus radiotherapy (IC+RT) in patients with locoregionally advanced nasopharyngeal carcinoma (NPC). Patients and Methods: 1324 patients with newly-diagnosed NPC treated with IC+CCRT or IC+RT were enrolled. Progression-free survival (PFS), distant metastasis-free survival (DMFS), overall survival (OS), locoregional relapse-free survival (LRFS), and acute toxicities during radiotherapy were compared using propensity score matching (PSM). A nomogram was developed to predict the 3- and 5-year PFS with or without concurrent chemotherapy (CC). Results: PSM assigned 387 patients to the IC+CCRT group and IC+RT group respectively. After 3 years, no significant difference in PFS (84.7% vs. 87.5%, P=0.080), OS (95.5% vs. 97.6%, P=0.123), DMFS (89.7% vs. 92.8%, P=0.134), or LRFS (94.0% vs. 94.1%, P=0.557) was noted between the groups. Subgroup analysis indicated comparable survival outcomes in low-risk NPC patients (II–III with EBV DNA<4000 copies/ml) between the groups, although IC+RT alone was associated with fewer acute toxicities. However, IC+CCRT was associated with significantly higher 3‑year PFS, OS, DMFS, and LRFS rates, relative to IC+RT alone, in high-risk NPC patients (IVa-b or EBV DNA≥4000 copies/ml). Multivariate analysis showed that T category, N category, EBV DNA level, and treatment group were predictive of PFS, and were hence incorporated into the nomogram. The nomogram predicted that the magnitude of benefit from CC could vary significantly. Conclusions: IC+RT had similar efficacy as IC+CCRT in low-risk NPC patients, but was associated with fewer acute toxicities. However, in high-risk patients, IC+CCRT was superior to IC+RT.